State Policies on Religious Diversity in Indonesia - M. Mujiburrahman (Al-Jami'ah: Journal of Islamic Studies, 2008)
This article discusses how Indonesian state manages its religious diversity. The state policies on religious diversity cannot be understood without analyzing the history of how the founding fathers decided to choose Indonesia as neither secular nor Islamic country, but somewhere between the two. The author discusses three topics, namely the recognized religions, muslim's fear of christianization, and dialogue and inter-religious harmony. Based on the Decree No.1/1965, Confucianism was one of six religions recognized by the state. However, in the Soeharto era, around 1979, this religion was dropped from the list, and only after his fall Confucianism has been rehabilitated, and even the Chinese New Year has been included as one of the national holidays in Indonesia. In terms of muslim-christian relations, there were tensions since 1960s, particularly dealt with the issue of the high number of Muslims who converted to Christianity. It was in this situation that in 1967 a newly built Methodist Church in Meulaboh, Aceh, was closed by Muslims, arguing that the Church was a concrete example of the aggressiveness of Christian missions because it was built in a Muslim majority area. Since the Meulaboh case, the Muslims consistently insisted the government to accommodate their four demands: (1) restriction on establishing new places of worship; (2) restriction onreligious propagation, and control of foreign aid for religious institutions; (4) Islamic religion classes should be given to Muslim students studying in Christian schools; (5) inter-religious marriage should not be allowed. Apart from these contested issues, the government and religious leaders have been trying to avoid conflict and to establish cooperation and peace among religious groups in the country through inter-religious dialogues, either organized by the government or sponsored by the leaders of religious groups themselves. The author argues that specific socio-political contexts should be taken into consideration to understand state policies making concerning religious diversity. Hence, all debates and compromises achieved afterwards usually do not go beyond the neither secular nor Islamic compromise.